Alzheimer’s disease and its associated risk of bone fractures: a narrative review - Zhou, Bing-Na; Zhang, Qian; Li, Mei (Frontiers in Endocrinology, 2023)
Background Alzheimer’s disease (AD) is a neurodegenerative disorder that is the major cause of dementia in the aged population. Recent researches indicate that patients with AD have a significantly increased fracture risk, but the pathological mechanisms are still unclear. Objective We systematically reviewed studies regarding bone fracture risk in AD to uncover links between the pathologies of osteoporosis and AD. Methods We searched the literature using the databases of PubMed, Web of Science, Embase and Cochrane Library. Studies were included if they evaluated bone fracture risk in AD patients and if they explored the pathogenesis and prevention of bone fractures in these patients. Results AD patients had a significantly higher risk of bone fractures than age-matched controls. Multiple factors contributed to the increased risk of bone fractures in AD patients, including the direct effects of amyloid pathology on bone cells, abnormal brain-bone interconnection, Wnt/β-catenin signalling deficits, reduced activity, high risk of falls and frailty, and chronic immune activity. Exercise, prevention of falls and fortified nutrition were beneficial for reducing the fracture risk in AD patients. However, the efficacy of anti-osteoporotic agents in preventing bone fractures should be further evaluated in AD patients as corresponding clinical studies are very scarce. Conclusion Alzheimer’s disease patients have increased bone fracture risk and decreased bone mineral density owing to multiple factors. Assessment of anti-osteoporotic agents’ efficacy in preventing bone fractures of AD patients is urgently needed.